ANALISIS KETERLIBATAN SISWA MENENGAH PERTAMA DALAM PEMBELAJARAN BERBASIS PROYEK PADA KURIKULUM MERDEKA - Napitupulu, Septyana Putri; Murniarti, Erni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This article aims to describe the involvement of junior high school students in project-based learning within the Merdeka Curriculum. The Merdeka Curriculum is an educational approach designed to provide autonomy to students and encourage their engagement in the learning process, thereby allowing them to fully develop their potential. This article uses a qualitative approach with literature study as the main approach in collecting data. Researchers also analyzed various literature sources, articles and scientific works related to junior high school students' participation in project-based learning in the context of the Merdeka Curriculum. Common challenges faced by junior high school students include a lack of understanding by educators, limited school support, and resource constraints. Therefore, this study aims to provide in-depth insights into project-based learning and how student involvement in learning within the Merdeka Curriculum can be enhanced.